Clinical Psychology Interns’ Lived Experiences With Suicidal Clients - Elayda, Elaine; Distor, John Mark (Journal of Interdisciplinary Perspectives, 2024)
This paper explores the lived experiences of clinical psychology interns who have encountered suicidal clients during their internship. Employing qualitative phenomenological investigation, semi-structured interviews were conducted and analyzed using interpretative phenomenological analysis (IPA). The study employed purposive sampling and gathered valuable data from 8 clinical psychology interns who were all taking a master's degree in Clinical Psychology. The results highlighted that those encounters with suicidal clients triggered various reactions among interns, leading to self-doubt and a sense of unpreparedness in handling such cases. Many interns struggled with managing their emotions, especially when clients' traumas mirrored their experiences. The study emphasized the importance of a robust support system in helping interns cope with the challenges of their work. The results included a heightened need for supervision among interns, as they faced intense emotional challenges when working with suicidal clients. Supervision emerged as a critical component in helping them process these experiences. Regular check-ins with supervisors not only provided emotional support but also offered practical strategies for managing client interactions. This guidance helped interns develop coping mechanisms and build resilience, fostering their professional growth and confidence in handling difficult cases. Despite the challenges, the interns found purpose in witnessing significant client progress and emphasized the importance of self-care and ongoing training to prepare future clinicians for similar experiences.